2017
DOI: 10.1080/19371918.2017.1327387
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Self-Reported Likelihood of Seeking Social Worker Help among People with Physical Disabilities

Abstract: The current study assesses the association between demographic factors, attitudes toward social workers, the stigma attached to seeking social worker help, perceived social support, and psychological distress-and the self-reported likelihood of seeking social worker help, among people with physical disabilities in Israel. Data collection utilized structured questionnaires, administered to a sample of 435 people with physical disabilities. The findings suggest that women, older respondents, people with more pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…In fact, although it is possible to utilize the professional services of SWs for a considerable part of the personal, family, and social issues people dealt with during this period, only some 18.7% of all respondents reported a high or very high likelihood of seeking their help. This number is significantly lower than that reported in studies that explored this issue in Israel in routine times ( Kagan & Zychlinski, 2017 ; Kagan et al, 2017 , 2018 ). Hence, in order to explain the likelihood of seeking help from SWs among the general population during the COVID-19 crisis, the contribution of select demographic and psychosocial variables and of prior experience with seeking or receiving help from SWs was examined.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…In fact, although it is possible to utilize the professional services of SWs for a considerable part of the personal, family, and social issues people dealt with during this period, only some 18.7% of all respondents reported a high or very high likelihood of seeking their help. This number is significantly lower than that reported in studies that explored this issue in Israel in routine times ( Kagan & Zychlinski, 2017 ; Kagan et al, 2017 , 2018 ). Hence, in order to explain the likelihood of seeking help from SWs among the general population during the COVID-19 crisis, the contribution of select demographic and psychosocial variables and of prior experience with seeking or receiving help from SWs was examined.…”
Section: Discussioncontrasting
confidence: 58%
“…Studies conducted on this subject in Israel, where the current study was carried out, show that fairly high proportions of the respondents reported a very low likelihood, or no likelihood at all, of seeking help from SWs. For instance, in two studies among the general population in Israel ( Kagan & Zychlinski, 2016 , 2017 ), such statements were made by 37.7% and 32.1% of the respondents, respectively, while among people with physical disabilities the proportion was 35% ( Kagan et al, 2017 ) and among older men 39% ( Kagan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of seeking help from social workers has received fairly limited research attention, focusing mainly on the general population ( Barwick et al, 2009 ; Kagan & Zychlinski, 2016 ) and on populations with specific characteristics, such as people with physical disabilities ( Kagan, Itzick, & Tal-Katz, 2017 ). Very few studies have been conducted with regard to seeking social workers’ help among older adults in general (e.g., Manthorpe, Moriarty, Rapaport, Clough, & Cornes, 2008 ) and older men in particular.…”
Section: Seeking Help From Social Workersmentioning
confidence: 99%